Pengelolaan Sumber Daya Perikanan Pada Wilayah Perbatasan Tanpa Perjanjian Bilateral - Moa, Maria Regina; Wattimena, Josina Augustina Yvonne; Tahamata, Lucia Charlota Octovina (Faculty of Law Universitas Pattimura, 2024)
The existence of the Republic of Indonesia has made this country recognized as an archipelagic country with many Indonesian archipelagos, so it is not surprising that there is a lot of potential fishery resources that can be managed, so the United Nations Convention on the Law of the Sea or called UNCLOS 1982. The Republic of Indonesia has many islands, so it is undeniable that Indonesia has many border areas with other countries. Border areas have a very important role in state sovereignty, but there are often problems in these areas, for example, illegal fishing often occurs, especially in the EEZ area, in UNCLOS 1982 in article 62 paragraph (2) has regulated related to the management of fishery resources in the EEZ and in article 51 paragraph (2) also regulates related to rights and Traditional Fshing Rights. Although the 1982 UNCLOS has been regulated, there are many findings that have occurred in the Indonesian EEZ area bordering Timor Leste. This research is normative juridical, namely the collection and analysis of primary, secondary, and tertiary data through literature studies. The data is analyzed qualitatively and systematically compiled by legal disciplines to provide clarity on the issues discussed. The results of this study show that there are several border areas between Indonesia and neighboring countries that have not been fully agreed, for example in the EEZ border area of Timor Leste and Indonesia which still overlaps and becomes an area where illegal fhising often occurs, this problem arises from the ship that was leased by Timor Leste from China to be included in the EEZ which Indonesia claimed that the area was its EEZ.